Pharmacokinetics of active compounds of a Terminalia chebula Retz. Ethanolic extract after oral administration rats using UPLC-MS/MS - Yao, Guangzhe; Miao, Xinxin; Wu, Mengxuan; Lv, Zhenguo; Bai, Yu; Chang, Yanxu; Ouyang, Huizi; He, Jun (Frontiers in Pharmacology, 2023)
Terminalia chebula Retz. (TC) is a well-known Chinese herbal medicine and rich in chemical components with multiple pharmacological effects. In this study, an ultra-performance liquid chromatography-tandem mass spectroscopy (UPLC-MS/MS) method was developed and used to determine the blood concentrations of nine active compounds (chebulic acid, gallic acid, protocatechuic acid, corilagin, chebulagic acid, chebulinic acid, 1,2,3,4,6-O-pentagalloylglucose, ellagic acid and ethyl gallate) after oral administration of TC extracts in rats. Pretreatment of plasma samples with protein precipitate with methanol was carried out, and caffeic acid was used as the internal standard (IS). Compounds precisions of intra- and inter-day were less than 14.6%, and the accuracy ranged from −11.7% to 13.5%. The extraction recoveries of compounds were between 84.9% and 108.4%, while matrix effects occurred between 86.4% and 115.9%. Stability tests showed that all nine analytes had been stable under four storage conditions, and statistically significant the relative standard deviations were under 13.7%. The validated UPLC-MS/MS method was applied with great success to plasma pharmacokinetics analysis of the TC extracts, and the pharmacokinetic results showed that among the nine components, the area under the concentration-time curve (AUC(0-tn), 231112.38 ± 64555.20 h ng/mL) and maximum concentration (Cmax, 4,983.57 ± 1721.53 ng/mL) of chebulagic acid were relatively large, which indicated that it had a higher level of plasma exposure. The half-life of elimination (T1/2) of chebulinic acid, corilagin and chebulagic acid were 43.30, 26.39 and 19.98 h, respectively, suggesting that these analytes showed prolonged retention and metabolize more slowly in vivo. This study would deliver a theoretical foundation for the further application of TC in clinical practice.